From deep to shallow fluid reservoirs: evolution of fluid sources during exhumation of the Sierra Almagrera, Betic Cordillera, Spain. Issue 1 (3rd May 2015) - Dyja, V.; Hibsch, C.; Tarantola, A.; Cathelineau, M.; Boiron, M.‐C.; Marignac, C.; Bartier, D.; Carrillo‐Rosúa, J.; Ruano, S. Morales; Boulvais, P.
Abstract: The combination of structural, geochemical and palaeotopographic data proves to be an efficient tool to understand fluid transfers in the crust. This study discriminates shallow and deep fluid reservoirs on both sides of the brittle–ductile transition under an extensional regime and points out the role of major transcurrent fault activity in this palaeohydrogeological setting. Palaeofluids trapped in quartz and siderite–barite veins record the transfer of fluids and metal solute species during the Neogene exhumation of the Sierra Almagrera metamorphic belt. Ductile then brittle–ductile extensional quartz veins formed from a deep fluid reservoir, trapping metamorphic secondary brines containing low‐density volatile phases derived from the dissolution of Triassic evaporites. During exhumation, low‐salinity fluids percolated within the brittle domain, as shown by transgranular fluid inclusion planes affecting previous veins. These observations indicate the opening of the system during Serravalian to early Tortonian times and provide evidence for the penetration of surficial fluids of meteoric or basinal origin into the upper part of the brittle–ductile transition. During exhumation, synsedimentary transcurrent tectonic processes occurred from late Tortonian times onwards, while marine conditions prevailed at the Earth's surface. At depth in the brittle domain, quartz veins associated with haematite record a return to high‐salinity fluid circulation suggesting an upward transfer fed from a lower reservoir. During the Messinian, ongoing activity of the trans‐Alboran tectono‐volcanic trend led to the formation of ore deposits. Reducing fluids caused the formation of siderite and pyrite ores. The subsequent formation of galena and barite may be related to an increase of temperature. The high salinity and Cl/Br ratio of the fluids suggest another source of secondary brine derived from dissolved Messinian evaporites, as corroborated by the δ 34 S signature of barite. These evaporites preceded the main sea‐level drop related to the peak of the salinity crisis (5.60–5.46 Ma). Abstract : The evolution of fluids in the Betic Cordillera points out the role of three main driving forces: 1) an exhumation path related to an overall cooling, 2) a drastic change to transcurrent tectonics associated with hydrogeological connections at depth favouring the ascent of hydrothermal fluids and, 3) the involvement of two types of secondary brines, an input from the deep reservoir involving Triassic evaporites and a input from the Messinian at the surface, which might have caused the concentration of economic elements.